Aspectos da diversidade de fungos filamentosos no brasil: a micobiota do solo do cerrado nativo e cultivado e o déficit wallaceano nos registros de macromicetos - Santos, Thales Antony de Assis (2018)
In the last century much has been discovered about the characteristics of fungal taxonomic groups, but there is still much to be discovered, including the geographical distribution of fungal species, which presents huge gaps. This work aimed to study some aspects of the diversity of filamentous fungi in Brazil, including the wallacean deficit in the macromicet records, the profile of the research on fungi of the soil of Cerrado, as much in scientific character as in the promotion of synthesis on this knowledge and the Micobiota of native and cultivated Cerrado soil. It was possible to observe that the closer to the research institutions, the greater the number of fungi recorded, so that the observed gaps intensify the Wallaceano Deficit. Scientometric analysis of the scientific production on soil fungi of Cerrado showed that the temporal distribution of the articles presented a pattern of homogeneity over the years. It was also noticed that a great part of the works were developed with FMs, using this symbiotic relation in favor of the improvement of the nutrient absorption by the agricultural crops. This draws attention to the fact that no work was really concerned about environmental issues. When comparing both the physicochemical characteristics and the abundance of Mycobiota (determined by the quantitative colony forming units - UFC) in native and cultivated Cerrado soils, no significant differences were found, regardless of the type of crop. This indicates that the management of cultivated soils did not practically alter their physical-chemical attributes, nor did it influence the abundance of the edaphic Mycobiota.